Efficacy of the Gottman Method on Family Cohesion and Emotional Self-Regulation Among Couples - Sarchuni, Somayeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Background and Objective: Couples face numerous challenges in marital life, particularly in areas of family cohesion and emotional self-regulation. Implementing psychological interventions to enhance these characteristics is essential. This study aimed to determine the effectiveness of couples therapy using the Gottman method on family cohesion and emotional self-regulation among couples. Methods and Materials: This quasi-experimental research was conducted using a pre-test and post-test design. The study population consisted of couples seeking divorce at counseling centers in Tehran in the year 2023. The sample comprised 50 couples, selected through convenience sampling and randomly assigned into two equal groups (each group containing 25 couples). The intervention group underwent eight 36-minute sessions (two sessions per week) of couples therapy using the Gottman method. Research tools included questionnaires on family cohesion and emotional self-regulation, completed by both groups during pre-test and post-test phases. Data were analyzed using multivariate analysis of covariance. Findings: Results indicated significant differences between the experimental and control groups in the post-test stage for the variables of family cohesion (F=54.29, p<0.001) and emotional self-regulation (F=11.40, p<0.001). Conclusion: The findings underscore the importance of couples therapy using the Gottman method in enhancing family cohesion and emotional self-regulation among couples. Consequently, clinical psychologists and therapists can utilize this method to improve psychological characteristics, particularly improving family cohesion and emotional self-regulation.